2020
DOI: 10.1186/s12884-020-03230-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of midwifery led counseling based on Gamble’s approach on childbirth fear and self-efficacy in nulligravida women

Abstract: Background Studies show that childbirth fear is a common problem among Iranian women. Therefore, most Iranian women prefer caesarean section for giving birth. This study investigated the effectiveness of a psychoeducational intervention by midwives (birth emotions - looking to improve expectant fear (BELIEF)) on decreasing childbirth fear and self-efficacy among first-time pregnant women who were afraid of giving birth. Methods A num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 23 publications
(47 reference statements)
1
35
2
Order By: Relevance
“…However, Firouzan et al revealed that midwifery-led counseling in pregnant women have reduced the choice of cesarean section as a delivery method. Although the finding of this study is not consistent with that of the present study, it can indicate the essential role of women in choosing the type of delivery and its influence on fathers [ 18 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, Firouzan et al revealed that midwifery-led counseling in pregnant women have reduced the choice of cesarean section as a delivery method. Although the finding of this study is not consistent with that of the present study, it can indicate the essential role of women in choosing the type of delivery and its influence on fathers [ 18 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study showed that midwifery-led counseling reduced the fathers’ fear of childbirth in the intervention group significantly. This finding is consistent with the previous studies that found out that midwifery-led counseling in two face-to-face sessions during the 24th and 34th weeks of pregnancy along with eight sessions of telephone counseling reduced the mothers’ fear of childbirth in the intervention group [ 18 ]. Similarly, Andaroon et al revealed that three sessions of individual counseling by the midwife during the 28th and 34th weeks of pregnancy reduced the mothers’ fear of childbirth in the intervention group [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…14 studies focused on "fear of childbirth" as an outcome (Abdollahi et al, 2020;Airo (Toivanen) et al, 2018;Amiri et al, 2019;Andaroon et al, 2017;Boryri et al, 2018;Boz et al, 2020;Firouzan et al, 2020;Haapio et al, 2017;Hildingsson et al, 2019;Irmak Vural & Aslan, 2019;Kacperczyk-Bartnik et al, 2019;Karabulut et al, 2016;Klabbers et al, 2019;Kordi et al, 2017;Larsson et al, in press;Mary et al, 2017;Munkhondya et al, 2020;Narita et al, 2018;Nieminen et al, 2016;Rahmani et al, 2019;Rondung et al, 2018;Rouhe et al, 2015b;Shahsavan et al, 2020;Swift et al, in press;Uçar & Golbasi, 2019).…”
Section: Outcome Variablesmentioning
confidence: 99%
“…Esfandiari et al (2020) showed that group supportive counselling scores of state-anxiety were reduced more remarkably than in the CG with a large effect size. Firouzan (2020) (2016) which also studied the effect of group cognitive behavioral therapy (GCBT) on state/trait anxiety during pregnancy. There was a significant decrease in the level of state and trait anxiety in the GCBT group before and after the intervention.…”
Section: Categories Of Interventionsmentioning
confidence: 99%